2015 International Conference on Electronics, Communications and Computers (CONIELECOMP) 2015
DOI: 10.1109/conielecomp.2015.7086928
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, simulation, and construction of a furuta pendulum test-bed

Abstract: This paper presents a Furuta pendulum as a testbed to experimentally validate automatic control strategies or theoretical concepts associated with nonlinear systems. Herein, the modeling, simulation, and construction of a Furuta pendulum test-bed are introduced step-by-step. The development of the Furuta pendulum mathematical model is achieved by using Lagrange equations of motion. In contrast with other works, the development of this model includes an analysis of the system kinematics. Also, a numerical simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…where L is the Lagrange relation obtained by combining both energy equations, K arm and k p are the kinetic energy equations of the arm and the pendulum respectively, meanwhile V arm and V p are their potential energy equations. After the kinetic and potential energies analysis, as explained in [18] and also validated by [11], the expansion of (1) leads to second order differential equations; the first one, is the differential equation of the motion of the pendulum in terms of the angle generated between the horizontal plane and the pendulum's arm (θ arm ). Meanwhile, the second one is the differential equation obtained from the motion of the system, in terms of the pendulum and the angle between the vertical axis and the pendulum itself (θ p ).…”
Section: System Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…where L is the Lagrange relation obtained by combining both energy equations, K arm and k p are the kinetic energy equations of the arm and the pendulum respectively, meanwhile V arm and V p are their potential energy equations. After the kinetic and potential energies analysis, as explained in [18] and also validated by [11], the expansion of (1) leads to second order differential equations; the first one, is the differential equation of the motion of the pendulum in terms of the angle generated between the horizontal plane and the pendulum's arm (θ arm ). Meanwhile, the second one is the differential equation obtained from the motion of the system, in terms of the pendulum and the angle between the vertical axis and the pendulum itself (θ p ).…”
Section: System Modellingmentioning
confidence: 99%
“…where the estimation of f (x) can be expressed as the product of the input values with the networks weights, as seen in (18).…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Most of the authors dealing with this problem mentioned the high complexity of the model, especially the friction effects arising from the wide range of velocities the links go through. The parameters representing the dry and viscous frictions in the joints are one of the most difficult parameters to identify [8], [14]- [20]. Indeed, there is no universal model to represent damping, and the literature contains several models that attempt to capture the physics of this complex phenomenon [21]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [1] and [7] proposed a linearized model based on a small angle assumption. Others neglected one or more of the cross coupling terms relating the two rotations [1], [3], [6], [8], [9]. The authors of [7] showed, through simulations, that the aforementioned assumption is not acceptable and it could have an important effect on the dynamic response.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [7] showed, through simulations, that the aforementioned assumption is not acceptable and it could have an important effect on the dynamic response. The authors of [8] derived a significantly simplified system and carried a brief three-second test. All the experimental works on the Furuta pendulum are directed at testing various control strategies [10], [11].…”
Section: Introductionmentioning
confidence: 99%